1976
DOI: 10.1177/00220345760550060501
|View full text |Cite
|
Sign up to set email alerts
|

Glass Ionomer Cements: Chemistry of Erosion

Abstract: A three-month study of the chemistry of the water erosion of two forms of ASPA cement has been made. The effect of varying cement consistency and cure time was investigated. The results are discussed in terms of the known chemistry and structure of the cement. The erosion behavior is compared to that of silicate, silicophosphate, and zinc polycarboxylate dental cements. The state of absorbed water and the mechanism of erosion is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 16 publications
2
34
2
3
Order By: Relevance
“…This was found to be in good agreement with the literature [21,46]. Wilson noted that higher molar mass cements failed with marked plastic deformation, while lower molar mass cements failed in a brittle fashion [21], confirming the Edwards model.…”
Section: Effect Of the Paa Molar Masssupporting
confidence: 87%
See 3 more Smart Citations
“…This was found to be in good agreement with the literature [21,46]. Wilson noted that higher molar mass cements failed with marked plastic deformation, while lower molar mass cements failed in a brittle fashion [21], confirming the Edwards model.…”
Section: Effect Of the Paa Molar Masssupporting
confidence: 87%
“…The strength of CGPCs increases quickly in the early stages of the reaction, within the first few days of maturation, and then increases at a slower rate over the following year [45,46]. It was first postulated by Crisp and Wilson [44] that this hardening process is based on the gelation of the polymeric acid by cross-linking, or forming inter-and intramolecular salt bridges, of the polymeric carboxyl groups with Al 3+ and Ca 2+ from the glass phase.…”
Section: The Role Of Paa During Cgpc Maturationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, they are free to move in and out of the cement. 6 Thus, GIC is considered to be a fluoride reservoir, maintaining a steady flow of fluoride ions into the surrounding tooth structure and enhancing resistance to caries attack throughout the life of the restoration. 7 In-vitro studies have shown that glass-ionomer cements can serve as rechargeable reservoirs, delivering a constant low level of fluoride due to uptake from fluoridated solutions, dentifrices and mouthwashes.…”
Section: Introductionmentioning
confidence: 99%